Baicalin–Zinc Complex Alleviates Inflammatory Responses and Hormone Profiles by Microbiome in Deoxynivalenol Induced Piglets - Zha, Andong; Tu, Ruiqi; Cui, Zhijuan; Qi, Ming; Liao, Simeng; Wang, Jing; Tan, Bie; Liao, Peng (Frontiers in Nutrition, 2021)
This study aimed to investigate the beneficial effect of baicalin-zinc complex (BZN) on intestinal microorganisms in deoxynivalenol (DON) challenged piglets and the association between intestinal microorganisms and host immunity and hormone secretion. Forty weaned piglets were randomly divided into 4 treatments with 10 piglets in each treatment: (1) Con group (pigs fed basal diet); (2) DON group (pigs fed 4 mg DON/kg basal diet); (3) BZN group (pigs fed 0.5% BZN basal diet); (4) DBZN group (pigs fed 4 mg DON/kg and 0.5% BZN basal diet). The experiment lasted for 14 days. BZN supplementation in DON contaminated diets changed the intestinal microbiota composition and increased intestinal microbial richness and diversity of piglets. BZN supplementation in DON contaminated diets also alleviated the inflammatory responses of piglets and modulated the secretion of hormones related to the growth axis. Moreover, the abundance of microbiota was associated with inflammatory and hormone secretion. In conclusion, BZN alleviated inflammatory response and hormone secretion in piglets, which is associated with the intestinal microbiome.